Total Physical Response and Early Language Development: Integrating Motivation, Action, and Reward in Pandemic Pedagogy - Malage, Gloria Risnawati; Mulyana, Indah (Jurnal Tahuri, 2024)
This article examines the implementation of the Total Physical Response (TPR) method in early English language learning during the Covid-19 pandemic by integrating the Motivation–Action–Reward framework. The study addresses the pedagogical challenges caused by the abrupt transition to online learning, which often reduces children’s motivation, engagement, and vocabulary acquisition. Using a descriptive qualitative method with a mini classroom ethnography approach, the research involved 15 children aged 5–6 years at TK Kristen Caritas Ambon. Data were collected through participant observation, documentation (photos, videos, anecdotal records), and informal interviews with teachers and parents. Thematic coding, language development assessments aligned with the Indonesian early childhood curriculum, and data triangulation were applied for analysis. The findings reveal that integrating Motivation–Action–Reward within TPR sustains children’s enthusiasm, enhances participation, and supports early language development, particularly in mastering basic vocabulary such as prepositions of place. Children responded positively to physical instructions, enjoyed online Zoom activities, and experienced intrinsic satisfaction from simple verbal rewards. The study’s novelty lies in systematically integrating TPR with a motivational framework for young learners in eastern Indonesia, a context rarely explored in international scholarship. The research contributes to education, linguistics, and language studies by expanding adaptive movement-based pedagogies for distance learning, enriching second language acquisition research for early EFL learners, and providing practical recommendations for teachers and policymakers.